Use of radiograph optical densitometry to monitor bone quality in broiler breeders - Paz, Ibiara Correia de Lima Almeida [UNESP]; Mendes, AA [UNESP]; Quinterio, RR [UNESP]; Vulcano, LC [UNESP]; Ballarin, Adriano Wagner [UNESP]; Takahashi, SE [UNESP]; Garcia, RG [UNESP]; Komiyama, CM [UNESP]; Balog, Augusto [UNESP]; Pelícia, K [UNESP]; Wescheler, FS [UNESP]; Scudeller, PSO [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2006)
This study was carried out at Faculdade de Medicina Veterinária e Zootecnia, Universidade Estadual Paulista, Botucatu, SP, Brazil, and evaluated bone quality in broiler breeders. Twenty-three families of Ross broiler breeders were housed in 5.0-m² pens. The families were comprised of 13 females and one male at the onset of the experimental period. The mean number of females per family was 9.34 at the end of the trial. The feeding program and management followed strain guidelines (Agroceres Ross, 2003). Bone analyses were performed in the right tibia and femur using optical radiographic densitometry at 4, 8, 12, 15, 20, 24, 30, 35, 42, 47 and 52 weeks of rearing. Trap nests were used to collect eggs from the breeders two weeks before and after the evaluation weeks. At each evaluation day, five birds were sacrificed after radiographs were taken and the tibias and femurs were collected to perform the following analyses: fatfree dry matter, ash percentage, bone resistance and Seedor index. Therefore, it was possible to establish correlations between bone quality and eggshell quality. Characteristics of bone quality were highly correlated to each other; on the other hand, there were no correlations between bone quality and external egg quality. In conclusion, there was no effect of egg production on egg quality, possibly because there was no reabsorption of bone minerals.
Keywords: Bone density; broiler breeders; eggshell quality; optical densitometry; Seedor index